HARGA, PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MOTOR YAMAHA MIO SERIES DI KARANGANYAR: Harga, Produk, Dan Citra Merek Terhadap Keputusan Pembelian Motor Yamaha Mio Series di Karanganyar - Yofhi Septian Panglipurningrum (Universitas Nahdlatul Ulama Sidoarjo, 2023)
The aim of this research is to examine the influence of independent variable (price, product, and brand image) on Yamaha mio seriesdependent variable on famous motorcycle dealer with questionnaire method to 100 respondents of Yamaha mio series motorcycle consumer in Karahanyar Papers obtained by purposive sampling (judgedment). Based on the results of the analysis shows that thevalidity and reliability test of all items of the questions submitted proved valid and reliable. The results of the classic assumption test show that initerdistribusi research normally, does not occur multicollinearity, heteroscedasticity, and autocorrelation in theregression model. The result of multiple linear coefficient equations shows that the independent variable (price, product and brand image) positively influence the dependent variable (purchasedecision) Yamaha mio series on the famous motorcycle dealer in Papahan Karanganyar. The result of t test shows that the independent variable (price, product and brand image) has significant effect on Yamaha mio series dependent variable on Dealer of Motorcycle in Karanganganyar. F test results show that there is a significant influencebetween the independent variables (price, product, and brand image)simultaneously to the dependent variable (purchase decision)Yamaha Mio Series On Dealer Motorcycle In PapahanKaranganyar.Meanwhile, the test result R2 (coefficient of determination) obtained Adjusted R Square value of 0.695, which means that the independentvariable (price, product, andbrand image) contributes 69.5% to the dependent variable (purchase decision) Yamaha Mio Series At Dealer Kondang Motor In Papanganyardanan 30.5% is influenced by other variables such as service quality, promotion and insurance costs.